Kajian Identifikasi Kerusakan: Rumah Gadang di Perkampungan Adat Nagari Sijunjung - Wongso, Jonny; Tela, I Nengah; Roza, Fielda; Afrimayetti, Rini (Universitas muhammadiyah palembang, 2023)
The Traditional Village of Jorong Padang Ranah and Tanah Bato Nagari Sijunjung still maintain 76 rumah gadang which have been designated as Cultural Conservation Areas. The gadang houses in this traditional village are made entirely of wood and are susceptible to weathering and damage to building elements. This study aims to analyze the condition of the damage to the rumah gadang building through the field observation method. The identification of damage to the rumah gadang building is one of the stages of activities that must be carried out in an overall restoration process. The method used is the field observation method through observing the condition of the elements of the rumah gadang building. Observations were made on the existing condition of damaged building elements, type of damage, level of damage and plans for its handling. Each damage condition is informed in detail accompanied by photos, pictures and required information. Management plans in the form of architectural restoration and structural repairs are also informed in detail along with photos, drawings and required information. The results of the identification will be used as a model of the damage identification document which is used as the basis for technical planning for the preservation of the rumah gadang in the future.